STUDY OF THE STABILITY OF COASTAL RECLAMATION SLOPES BY USING GEOTEXTILES AS SOIL STRENGTH - Januario D C Fernandes (Neutron, 2019)
This study presents a simulation of coastal reclamation deposits with geotextiles in areas with the weakest soil profile. Case studies related to deeds and improvement of slopes with woven geotextiles. Observations and investigations show that the land is sand soil which has a low carrying capacity. Weak soil parametric effects, geotextile webbing, external loads, and earthquake loads were analyzed by PLAXIS. The calculation results show reinforcement with woven geotextiles and against external loads and earthquake loads, having a large safety factor.